Math, asked by saini0553, 1 year ago

(a+b+c)^2 - (a-b-c)^2​

Answers

Answered by Anonymous
1

 \huge \bold \red{hloo \: mate}

_______________________________

(a+b+c)^2 – (a-b-c)^2

This equation is of the form

x^2 – y^2= (x+y)(x-y)

If we apply this formula for the equation we get

(a+b+c)^2 – (a-b-c)^2

=(a+b+c+a-b-c){a+b+c-(a-b-c)}

=(2a)(a+b+c-a+b+c)

=(2a)(2b+2c)

=4ab + 4ac

__________________________

 \bold {hope \: it \: helps}

❤️❤️❤️❤️❤️❤️❤️❤️❤️

@AMANSAINI

Answered by shubhisaravgi
1

x²-y²=(x+y)(x-y)

(a+b+c+a-b-c)(a+b+c-a+b+c)

(2a)(2b+2c)

4ab +4ac

4(ab+ac)


Ritiksuglan: hi
Ritiksuglan: hanji
saini0553: hey
Similar questions